Improving Railway Punctuality: A Comparative Multi-Criteria Analysis of Solutions Across Six Nations - Ek, Ludvig; Gkaintatzis , Theodoros (My University, 2025)
This project is a part of a master’s program course named “Project in Railway Technology”, with 7.5 ECTS credits. The report analyzes the issue of punctuality of railways in six nations – Sweden, Greece, Japan, Finland, Germany and France – and observes the massive variations between the quality of infrastructure, operating efficiency and investment. It evaluates three principal solutions to improve punctuality: enhancing from single to double tracks, running dedicated high-speed trains, and timetabling. In a Multi-Criteria Decision Analysis (MCDA), the report compares these approaches in terms of cost, safety, capacity and time to implement, taking into consideration the perspective of various stakeholders, such as rail operators and travelers. The findings of the MCDA suggest that while investments in infrastructure guarantee longer term benefits, timetabling is a cheap and simple measure to adopt in order to increase punctuality. It concludes that railway punctuality must not only be improved through technical aspect, but also through strategic planning and cooperation of stakeholders.